Penerapan Sistem Informasi Geografis dan AHP Untuk Klasifikasi Masyarakat - Supriyono, Supriyono; Mustafid, Mustafid; Sugiharto, Aris (Universitas Diponegoro, 2011)
Geographic information system useful to the government's classifications to determine the priority of the welfare of society. While the criteria used are 6 criteria and 14 sub criteria and their implementation is still done by manual. The method used in the study